2003
DOI: 10.1071/ar02241
|View full text |Cite
|
Sign up to set email alerts
|

Supplementation of a tropical grass diet with forage legumes and Sapindus saponaria fruits: effects on in vitro ruminal nitrogen turnover and methanogenesis

Abstract: In two in vitro experiments with the RUSITEC-apparatus, Brachiaria dictyoneura was tested alone and with legumes at dietary proportions of 1/3, 2/3, or 3/3 of Arachis pintoi (Expt 1) and 1/3 of Arachis pintoi, Cratylia argentea, or Calliandra calothyrsus (Expt 2). In Expt 2, all diets were evaluated with and without 80 mg/g diet of Sapindus saponaria fruits. In Expt 1, the stepwise replacement of the grass by A. pintoi curvi-linearly increased rumen fluid concentrations of ammonia, volatile fatty acids, bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
85
1
25

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 135 publications
(126 citation statements)
references
References 33 publications
15
85
1
25
Order By: Relevance
“…Despite this widely known and predictable feed shortage cycle (see, e.g., Gryseels and Anderson, 1983;Hary et al, 1996) only few farmers grew fodder plants consisting of legumes or nutritious grasses, which could have contributed highly to improving livestock feeding practices and soil conservation (Conant et al, 2001;Hess et al, 2003;Powell and Mohamed-Saleem, 1987). This phenomenon might be due to competing land use interests on rather small properties as was also recognized by Saleem (1998).…”
Section: Animal Feed and Dung Usementioning
confidence: 93%
“…Despite this widely known and predictable feed shortage cycle (see, e.g., Gryseels and Anderson, 1983;Hary et al, 1996) only few farmers grew fodder plants consisting of legumes or nutritious grasses, which could have contributed highly to improving livestock feeding practices and soil conservation (Conant et al, 2001;Hess et al, 2003;Powell and Mohamed-Saleem, 1987). This phenomenon might be due to competing land use interests on rather small properties as was also recognized by Saleem (1998).…”
Section: Animal Feed and Dung Usementioning
confidence: 93%
“…Los taninos presentes en muchas leguminosas, como Calliandra calothyrsus, pueden estar asociados con la reducción en la producción de CH 4 , hasta en un 50%, respecto a la dieta tradicional de pasto solo (Hess et al, 2002). Relacionado con lo anterior, Molina et al (2013), a través de la técnica in vitro de producción de gases, incubaron Leucaena (Leucaena leucocephala) y pasto Guinea (Megathyrsus maximus).…”
Section: Efecto De Los Msp De Algunas Forrajeras Arbustivas Y Arbóreunclassified
“…By contrast, this supplementation strategy has hardly been adopted by farmers in Colombia, where other legume trees such as Cratylia argentea are frequently used to supplement ruminant livestock during the dry season (Plazas and Lascano 2005). A previous in vitro study demonstrated that the supplementation of a low-quality grass with Calliandra grown in a site with acid, low-fertility soils in Colombia apparently does not improve the feeding value of the complete diet (Hess et al 2003). However, there are certain indications that the feeding value of Calliandra could be affected by the cultivation site ).…”
Section: Introductionmentioning
confidence: 95%
“…More recently, research has focused attention on the nutritional value of Calliandra. Although having a favourably high protein content Tuwei et al 2003), reports of very high condensed tannin contents and low digestibility (Maasdorp et al 1999;Hess et al 2003;Lascano et al 2003) have questioned its value as a supplement for ruminants fed low-quality forage. Nevertheless, on-farm trials with dairy animals in the Embu area of Kenya have suggested that Calliandra can substitute concentrate without adverse effects on milk yield (Paterson et al 1999).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation